Development of Chemistry Flashcard (Chemilard) Based on Augmented Reality in Unity 3D for Chemical Bonding Material - Setiawan, Riky; Harahap, Lenni Khotimah (Journal of Educational Chemistry (JEC), 2024)
The lack of variety in instructional media can be a starting point for the difficulty in creating an effective and enjoyable learning environment, particularly in chemistry subjects. The concepts in chemical bonding are abstract, making them difficult to apply contextually. Based on these issues, the researchers developed CHEMILARD (Chemistry Flashcard) media using augmented reality. This research employed the D&D (Design and Development) model. The subjects of this study were 6 expert validators in media and content, as well as 25 respondents. The data analysis techniques included Aiken’s analysis and percentage models. The study concluded that the validation of CHEMILARD media, developed across all assessment aspects, indicated that the product is feasible for trial implementation with a score of V=0.90 from media experts and V=0.91 from content experts. The respondents' test results showed an ideal media percentage of 90.3% and an overall media quality rating of 76.72, which is categorized as Very Good. This indicates that the augmented reality-based CHEMILARD media can significantly enhance the learning experience by making abstract chemical bonding concepts more tangible and easier to understand for students.